From “Jewish Memory” to Jewish History - Chazan, Robert (The journal of Jewish thought & philosophy, 2017)
In his influential Zakhor: Jewish History and Jewish Memory, Yosef Hayim Yerushalmi analyzed brilliantly the transition in Jewish conceptions of Jewish history from premodern to modern times. The present paper discusses a number of alternative perspectives on this transition. Yerushalmi argued convincingly the importance of the traditional conception of Jewish history, which he labeled “Jewish memory,” for Jewish survival. This paper challenges the terminology, agrees with the role played by the traditional Jewish thinking in Jewish survival, and emphasizes the premodern circumstances that made the traditional thinking so vital and effective. With respect to modern conceptions of Jewish history, which Yerushalmi associates with Jewish history writing, this paper argues that an examination of the circumstances of modernity reveals the creativity of this altered view of the Jewish past and the ways in which it in turn has fostered Jewish survival in the face of radically new challenges.